The Effect of Financial Ratio on Company Value With Dividend Policy as a Moderation on the IDX30 Index - Subhanulfikri, Faiz; Wikartika, Ira (PT FORMOSA CENDEKIA GLOBAL, 2024)
Company worth is extremely essential since it demonstrates the business's overall accomplishment. The concept of signaling describes how firms feel compelled for communicate monetary report statistics regarding outside stakeholders to avoid information asymmetry. That investigation's audience consists of 49 firms included in the IDX30 index from 2020 to 2023. The sample for this research consisted of 16 issuers who had been selected using a purposive sampling technique, then multiplied by 4 according to the research period so that there were 64 samples. The moderated regression analysis (MRA) method is utilized to examine information using tools such as the SPSS application. The analysis results prove profitability has a destructive contribution to company value, liquidity has little impact on firm value, and solvency has a contribution to company value. Apart from that, dividend policy can limit the impact of profitability on company value; however, this can't reduce its effect of liquidity and solvency on the worth of the company.